An analysis of where the transfer pricing rules and the controlled foreign company rules interact: application to intra-group loans - Kamoetie, Diwa (University of the Witwatersrand, Johannesburg Date of Issue *, 2022)
It has become increasingly important for South African tax residents to correctly reflect an arm’s length price for which they transfer goods or services, and in the case of intellectual property, grant a use, right of use or permission to use of the intellectual property, to non- residents, as this may attract adverse tax consequences for failure to do so. This is of particular importance when funding cross-border operations. Furthermore, the ownership structure of the non-resident is also of importance, as the ownership structure adopted by the non-resident may have South African income tax consequences, for the South African tax resident, if that non-resident is a connected person to the South African tax resident,1 the non- resident is a controlled foreign company as defined in section 9D of the Income Tax Act, or both instances are applicable. Therefore, the controlled foreign company rules and the transfer pricing rules must be considered,2 amongst other factors, when engaging in cross- border tax structuring to correctly structure these transactions This research report critically examines the South African transfer pricing rules and South African controlled foreign company rules and discusses the overlap of the two sets of rules. This analysis goes further in identifying the means to manage transfer pricing risk using a controlled foreign company in relation to a South African taxpayer, with a specific focus on intro-group loans
A research report submitted to the Faculty of Commerce, Law and Management in partial fulfilment of the requirements for the degree of Master of Commerce (Taxation)
Keywords: Anti-avoidance; Arm’s Length Principle; Associated Enterprise; Comparable Uncontrolled Price; Connected Person; Controlled Foreign Company; Foreign Business Establishment; OECD Transfer Pricing Guidelines; Profit Split Method; Resale Method; Thin Capitalisation; UCTD; SDG-8: Decent work and economic growth